2017
DOI: 10.1016/j.jempfin.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The evolving beta-liquidity relationship of hedge funds

Abstract: Using an optimal changepoint approach, we find a structural change in the relation between hedge funds' stock market exposure and aggregate stock market liquidity that takes place in the period 2000 to 2002. Before the structural break, market betas have no relation to liquidity and only a few style categories of hedge funds show increased market presence when liquidity is low. After the break, the relationship is inverted, pointing towards an increased liquidity timing ability of hedge funds, as users of liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…While share restrictions allow funds to manage illiquid assets effectively in the pre-crisis period, they are insufficient to ensure effective management of illiquid portfolios during the crisis. Siegmann and Stefanova (2017) find that equity-focused HFs show a significant shift from negative to positive relation between market beta and liquidity after the major market microstructure changes in 2000. Teo (2011) finds that the return impact of fund flows is stronger when funds embrace liquidity risk, when market liquidity is low and when funding liquidity is tight.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 83%
“…While share restrictions allow funds to manage illiquid assets effectively in the pre-crisis period, they are insufficient to ensure effective management of illiquid portfolios during the crisis. Siegmann and Stefanova (2017) find that equity-focused HFs show a significant shift from negative to positive relation between market beta and liquidity after the major market microstructure changes in 2000. Teo (2011) finds that the return impact of fund flows is stronger when funds embrace liquidity risk, when market liquidity is low and when funding liquidity is tight.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 83%
“…Wattanatorn et al ( 2020 ) suggested that high-performing fund managers exhibit significantly positive liquidity timing skills while low-performing fund managers don’t demonstrate this behavior. Siegmann and Stefanova ( 2017 ) found evidence that equity- oriented hedge fund managers possess liquidity timing ability after the major market microstructure evolution in the year 2000. Recently, the empirical evidence supports the notion that hedge fund managers time market volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Criton and Scaillet (2011) further study whether hedge fund exposures display structural breaks in turmoil periods. Siegmann and Stefanova (2017) find optimal change-points in the beta-liquidity relationship in periods that feature either market turmoil or structural changes. Accordingly, structural change-point regression best captures rapid and sharp transitions in fund exposures, while state-space models best model smooth transitions.…”
Section: Dynamic Pricing Modelsmentioning
confidence: 99%